(untitled) (Palimpsesto, 2024)
Between the 15th and 25th of 1972, the government of Salvador Allende faced an international crisis when militants from the People’s Revolutionary Army (ERP), Revolutionary Armed Forces (FAR) and Montoneros organized the hit-and-run from the Rawson prison while a commando hijacked a plane to take them to Chile and later to Cuba. Those who did not manage to board were detained and later shot at the Alte air-naval base. Zar in Trelew. President Salvador Allende faced pressure from the Argentine government and a constant public debate about the political and legal consequences of granting asylum, allowing them passage to a third country or returning them to Argentina with the risk of being executed, while the right began the boycott of the month of October of that year.